EFEKTIVITAS PENGENDALIAN PENYAKIT KARAT KEDELAI DENGAN FUNGISIDA ALAMI - Heriyanto, Heriyanto (Jurnal Ilmu-Ilmu Pertanian, 2016)
Soybean rust disease is caused by Phakopsora pachyrhizi Syd fungus. It was important because the disease was contagious and there is always an attack in soybean farming, resulting in yield loss varied from 10-70 percent, but most farmers did not conduct controlling due to the expensive price of synthetic fungicides. In nature there are many mineral materials and plants that are toxic to microorganisms, further research in order to know the type of natural ingredients and effective doses in controlling rust diseases on soybean was carried out in the Banguntapan village, Banguntapan district, Bantul regency, from March to October 2015. Research was performed using randomized complete block design comprises 5 treatments use natural ingredients for controlling rust disease of soybean were clove oil (3 cc / l of water), prusi (CuSO4) and lime [Ca (OH)2] solution mixture, sulphur (S) with lime, salt (NaCl) solution with a concentration of 3 grams / l of water and water as a control, with replication as many as 4 times each treatment. Application is done by spraying the leaves beginning the age of 14 days after planting to 70 days with an interval of 7 days. The results showed that treatment with a mixed solution of prusi control with lime concentration of 3 grams in 1 litre of water showed effective results based on the analysis of the incubation period and percentage of diseased leaf and can reduce the intensity of rust disease by 26.84 percent.